MICROBIOLOGICAL ANALYSIS AND CMT-BASED DETECTION OF SUBCLINICAL MASTITIS IN BALI’S SOW PIGS - Romy Muhammad Dary Mufa; I Wayan Suardana; I Made Sukada; Kadek Karang Agustina (Buletin Veteriner Udayana, 2025)
Subclinical mastitis in sows (Sus scrofa) poses significant risks to pig health and breeding efficiency, particularly in Gianyar Regency, Bali. Early detection using the California Mastitis Test (CMT), followed by microbiological confirmation, is critical for effective management. This study aimed to evaluate subclinical mastitis in lactating sows using CMT and identify causative pathogens through laboratory tests. Milk samples from 30 lactating sows were analyzed. CMT-positive samples were cultured on selective media: Mannitol Salt Agar (MSA) for Staphylococcus aureus, Xylose Lysine Deoxycholate (XLD) for Salmonella, and Eosin Methylene Blue Agar (EMBA) for Escherichia coli. CMT detected subclinical mastitis in 21 sows (70%). Microbiological tests identified S. aureus (7 samples), Salmonella (2 samples), and E. coli (12 samples). CMT is an effective field tool for early mastitis detection. The high prevalence of pathogens, particularly E. coli, underscores the need for improved hygiene and targeted therapies in pig breeding environments.